The Influence of Motivation and Job Competence on Employee Performance in the Marketing of ABC Insurance - Ulfah Arini, Dewi; Suryadi, Rudi; Khairunnisa, Khairunnisa (Riviera Publishing, 2023)
This study aims to determine the effect of the motivation and work competence of ABC Insurance telemarketing through the Vinnocomm application on employee performance. The research design and methods were tested using multiple regression, and the instruments for each variable were tested using a descriptive presentation analysis before the partial effect test was carried out. The research sample was ABC Insurance exceptional telemarketing employees who had used the Vinnocomm Application as many as 65 respondents filling out a questionnaire. Validity and reliability tests, normality tests, multiple linear regression analysis, t-test, F-test, and coefficient of determination were carried out in the analysis phase. From the study results, telemarketing work motivation is quite influential in achieving performance but not too strong. Meanwhile, telemarketing work competence through the vinnocomm application has a significant and robust influence on the process of achieving the performance of telemarketers. This research has implications that it is necessary to increase enthusiasm and enthusiasm from telemarketing in carrying out work processes such as training, refreshment, periodic motivation, or in the form of bonuses and compensation that is in line with the results achieved from telemarketing.